Chapter 24 Quiz 1: Brownian Motion and Markov Process: Problems and Tentative Solutions
Exercise 24.1 (View Brownian motion as a special Gaussian process) Let W={Wt:t≥0} be a Brownian motion. Show that a Brownian motion can be viewed as a Gaussian process with mean 0 and Cov(Ws,Wt)=min.
Proof. Consider any finite dimensional distribution of W, denoted as F_{W_{t_1},\cdots,W_{t_k}}(w_{t_1},\cdots,w_{t_k}), w.l.o.g. we can assume t_1<\cdots<t_k and for simplicity of notation, we can surpass t and just denote the f.d.d.s. as F_{W_1,\cdots,W_k}(w_1,\cdots,w_k). Firstly, from the independent increment property and W_t-W_s\sim N(0,t-s) for 0\leq s\leq t, since W_1,\cdots,W_k can be expressed as a linear combination of independent normally distributed random variable W_1,W_2-W_1,\cdots,W_k-W_{k-1}, we have the f.d.d.s. of W is normally distributed. The mean is E(W_t)=0 and variance Var(W_t)=t, while the covariance is, assume w.l.o.g. s<t \begin{equation} \begin{split} Cov(W_sW_t)&=E(W_sW_t)=E(W_s(W_t-W_s+W_s))\\ &=E(W_s^2)+E(W_s)E(W_t-W_s)=s \end{split} \tag{24.1} \end{equation} Thus, the Brownian motion is a Gaussian process with mean function 0 and covariance function Cov(W_s,W_t)=\min\{s,t\}.
Proof. For h and t such that t\in[0,1] and h+t\in[0,1], we have \begin{equation} \begin{split} B_{t+h}-B_t&=W_{t+h}-(t+h)W_1-W_t+tW_1\\ &=(W_{t+h}-W_t)-hW_1\\ &=W_{t+h}-W_t-h(W_1-W_{t+h})-hW_{t+h}\\ &=(1-h)(W_{t+h}-W_t)-h(W_1-W_{t+h})-hW_t\\ \end{split} \tag{24.2} \end{equation}
Where W_t is a Brownian motion. By definition, we have W_{t+h}-W_t, W_1-W_{t+h} and W_t mutually independent, and W_{t+h}-W_t\sim N(0,h), W_1-W_{t+h}\sim N(0,1-h-t) and W_t\sim N(0,t). Thus, B_{t+h}-B_t also has a normal distribution with mean E(B_{t+h}-B_t)=0 and variance \begin{equation} Var(B_{t+h}-B_t)=(1-h)^2\cdot h+h^2(1-h-t)+h^2t=h(1-h) \tag{24.3} \end{equation}
Therefore, B_{t+h}-B_t\sim N(0,h(1-h)) which is not related to t. Thus, it has stationary increments.
Proof. Consider a stochastic process X=\{X(t,\omega):t\in\mathcal{T},\omega\in\Omega\} that has independent increments. Then for any t_1<t_2<\cdots<t_n and any s, we have \begin{equation} \begin{split} &P(X_{t_n}=s|X_{t_1}=x_1,\cdots,X_{t_{n-1}}=x_{n-1})\\ &=P(X_{t_n}-X_{t_{n-1}}=s-x_{n-1}|X_{t_1}=x_1,X_{t_2}-X_{t_1}=x_2-x_1,\\ &X_{t_3}-X_{t_2}=x_3-x_2,\cdots,X_{t_{n-1}}-X_{t_{n-2}}=x_{n-1}-x_{n-2})\\ &=P(X_{t_n}-X_{t_{n-1}}=s-x_{n-1})\quad (by\,independence)\\ &=P(X_{t_n}-X_{t_{n-1}}=s-x_{n-1}|X_{t_{n-1}}=x_{n-1})\\ &=P(X_{t_n}=s|X_{t_{n-1}}=x_{n-1}) \end{split} \tag{24.4} \end{equation} Therefore, by defintion of Markov process, we know that X is actually a Markov process.
Exercise 24.4 (Equivalent definition for Markov property) For a stochastic process \{X_n:n\geq 1\}, show that (a) and (b) are equivalent.
(a). It has Markow property, i.e. \begin{equation} P(X_{n+1}=x_{n+1}|X_n=x_n,\cdots,X_1=x_1)=P(X_{n+1}=x_{n+1}|X_n=x_n) \tag{24.5} \end{equation}
(b). For all finite sets of time points \{l\in L:1\leq l<n\} and \{k\in K:k>n\}, \begin{equation} \begin{split} P&(\{X_k=x_k,k\in K\},\{X_l=x_l,l\in L\}|X_n=x_n)\\ &=P(\{X_k=x_k,k\in K\}|X_n=x_n)P(\{X_l=x_l,l\in L\}|X_n=x_n) \end{split} \tag{24.6} \end{equation} i.e. past given the present is independent of future given the present.Proof. We first show (a) \Longrightarrow (b). Consider \{l\in L:1\leq l<n\} and \{k\in K:k>n\}, we have \begin{equation} \begin{split} P&(\{X_k=x_k,k\in K\},\{X_l=x_l,l\in L\}|X_n=x_n)\\ &=P(\{X_k=x_k,k\in K\}|\{X_l=x_l,l\in L\},X_n=x_n)P(\{X_l=x_l,l\in L\}|X_n=x_n)\\ &=P(\{X_k=x_k,k\in K\}|X_n=x_n)P(\{X_l=x_l,l\in L\}|X_n=x_n)\quad (\text{By Markov property}) \end{split} \tag{24.7} \end{equation} Therefore, we have (a) \Longrightarrow (b).
Now, for (b) \Longrightarrow (a), take set K=\{n+1\} and L=\{1,2,\cdots,n-1\}, then from (b) we have \begin{equation} \begin{split} P&(X_{n+1}=x_{n+1},X_{n-1}=x_{n-1},\cdots,X_1=x_1|X_n=x_n)\\ &=P(X_{n+1}=x_{n+1}|X_n=x_n)P(X_{n-1}=x_{n-1},\cdots,X_1=x_1|X_n=x_n) \end{split} \tag{24.8} \end{equation} On the other hand, \begin{equation} \begin{split} P&(X_{n+1}=x_{n+1},X_{n-1}=x_{n-1},\cdots,X_1=x_1|X_n=x_n)\\ &=P(X_{n+1}=x_{n+1}|X_n=x_n,X_{n-1}=x_{n-1},\cdots,X_1=x_1)\\ &\times P(X_{n-1}=x_{n-1},\cdots,X_1=x_1|X_n=x_n) \end{split} \tag{24.9} \end{equation} Compare (24.8) and (24.9) we can find \begin{equation} P(X_{n+1}=x_{n+1}|X_n=x_n,\cdots,X_1=x_1)=P(X_{n+1}=x_{n+1}|X_n=x_n) \tag{24.10} \end{equation} which is just (a), so we have (b) \Longrightarrow (a) as well.
In conclusion, (a) \Longleftrightarrow (b).